Water induced morphological transformation of a poly(aryl ether) dendron amphiphile: helical fibers to nanorods, as light-harvesting antenna systems - Maity, Arunava; Dey, Ananta; Gangopadhyay, Monalisa; Das, Amitava (Nanoscale, 2018)
Self-assembly of suitable molecular building blocks is an efficient and convenient approach to generate nanomaterials with various morphologies and functions. Moreover, understanding the nature of molecules and controlling factors of their self-assembly process is crucial in fundamental aspects of molecular self-assembly which provide insights into the design of new assemblies with functional nano-architectures. To this end, the present study reports water induced self-assembled multifaceted morphology formation and the plausible pathway of the morphology transformation of a single poly(aryl ether) dendron amphiphile 1(D). In THF, 1(D) self-assembles into helical fibers. However, with an increase in the water fraction in its THF solution, the morphology changes to nanorods through an intermediate scroll-up pathway of exfoliated fibers. The nanorod formation and transformation of 1(D) are investigated using various microscopy and spectroscopy techniques, which indicate that it has highly ordered multilayered arrays of 1(D) molecules. Finally, these multilayered arrays of 1(D) nanorods are exploited for constructing a model light-harvesting system via the incorporation of small quantities of two newly designed BODIPY based molecules as energy acceptors and 1(D) as an antenna chromophore.